External Treatment of Broiler Chickens with Lactic-Acid-Producing Bacteria Before Slaughter - Cason, J.A.; Buhr, R.J.; Hinton, A.; Jr.; Berrang, M.E.; Cox, N.A. (International Journal of Poultry Science, 2005)
Lactic-acid-producing bacterial cultures were applied to the skin of live broilers 24 hours before slaughter to determine whether inoculation with the cultures could affect the numbers of bacteria that are normally found on the skin of processed broiler carcasses. The cultures contained 10,000 to 100,000 cfu/mL and were suspended in 250 mL of a pH 6.0 nutrient medium (including glucose, peptone, beef extract, yeast extract, a surfactant, and salts) intended to enhance the survival and growth of the cultures. With broilers suspended by the feet, feathers were moved aside and the liquid suspension was sprayed directly on the skin. Sprayed broilers were then returned to a pen. In each of three replications, 4 six-wk-old broilers were sprayed and 4 broilers were kept as untreated controls. The following day, broilers were processed in a research processing facility and defeathered carcasses were sampled by rinsing for 1 min in 200 mL of peptone water after removal of heads and feet. Coliforms, E. coli, lactic-acid bacteria, and Campylobacter in carcass rinses were enumerated by standard methods. After removal of aliquots for plating, the remaining sample volume was enriched to detect Salmonella. No differences were found in log10(cfu/mL) of coliforms, E. coli, or lactic-acid bacteria between the treated and control carcasses. Salmonella bacteria were present on some carcasses, but with no difference between treatments. Campylobacter spp. were present in only one replication, so numbers of Campylobacter could not be analyzed statistically. Spraying lactic-acid-producing bacteria with nutrients on the skin of live broilers on the day before processing appears to have no effect on numbers of bacteria that are present on the skin after defeathering.